PROSES KONSTRUKSI MAKNA DALAM BAHASA JAWA DAN INDONESIA - Nirmala, Deli (LITERA, 2015)
Abstract This study aims to describe meaning construction processes in Javanese and Indonesian. It employed cognitive linguistic theories. The data sources were written and spoken languages in newspapers, books on Javanese and Indonesian proverbs, and conversations. The data were collected through the documentation and reflective-instrospective methods. They were analyzed using the referential and abductive inferential methods. Based on the results of the analysis, it can be concluded that meanings are constructed based on the experiences embodied in a human’s mind through a conceptualization process. There are facts showing how meanings are constructed, for example, metaphors, proverbs, derivational forms, three language metafunctions, and a variety of language uses in different situations. Keywords: meaning, construction